Body composition, energy expenditure, physical activity and association with metabolic syndrome in Malay children aged 9 to 14 years old - Wee Bee Suan
The aim of this cross-sectional study was to investigate the associations of body composition and energy expenditure with metabolic syndrome (MS) and to develop predictive equations for body composition for Malaysian children. A total of 408 healthy Malay children (207 boys; 201 girls) aged 9 to 14 years were recruited from government schools in Kuala Lumpur by cluster sampling method. Weight, height waist circumference (WC), skinfolds and blood pressure (BP) were measured. Body composition was assessed by bioelectrical impedance analysis and deuterium dilution (DO), total energy expenditure (TEE) by doubly labeled water (DLW) technique, resting metabolic rate (RMR) by indirect calorimetry, physical activity by pedometers and Actical accelerometers in a sub-sample. Tanner stages for pubertal development was self-assessed. Fasting blood glucose (FBG), triglycerides (TG), high-density lipoprotein (HDL-C), low density lipoprotein (LDC-C), total cholestrol (TC) and insulin were determined in an overnight fasting blood sample. WHO 2007 BMI- for-age z-score was used to group subjects into overweight/obese (O/O) and non-O/O categories. IDF (2007) criteria for children were used to diagnose MS while homeostasis model assessment (HOMA-IR) method was use to calculate insulin resistance (IR). Some 30.9% of children O/O. MS was found in 2.5% of O/O group but none in non-O/O group (p<0.001). IR prevalence was 14.5%, with O/O (84.7%) having higher prevalence than non-O/O (15.3%)(p<0.001). WC [0.864 (0.817, 0.912], waist height ratio (WHtR) [0.861 (0.812. 0.910)], BMI [0.856 (0.808, 0.904], body adiposity index [0.835 (0.779, 0.890] and visceral adiposity index [0.805 (0.749, 0.862], have similar discrimination in identifying IR risk. A HOMA-IR cut-off of 2.8 was found as the best threshold in identifying IR. Age (p<0.05), sex (p<0.05) and weight category (p<0.001) significantly influence IR. Predictive equations using DO criterion for estimation of total body water: TBW (kg) = [(0.549 x age (year)] + [0.248 x weight (kg)] + [(0.056 x height (cm)] + [(0.207 x resistance index + [(0.676 x sex (male=1, female=0] - (0.100 x TS (cm)] - 9.348 and fat free mass: FFM (kg) = (0.867 x age (year)] + (0.070 x height (cm)] + (0.280 x resistance index + (1.207 x sex (male=1, female=0)] - (0.136 x TS (cm)] - 13.655. Mean pedometer step count was significantly higher in boys than girls (12, 383 vs 8670) (p<0.001). Only 56.4% of children met the daily steps recommendation. The O/O group had significantly higher RMR (1455 kcal/day vs 1223 kcal/day) (p<0.001), activity energy expenditure (544 kcal/day vs 376 kcal/day)( (p<0.001) and TEE (2618 kcal/day vs 2061 kcal/day)(p<0.001) than non-O/O group. Predictive equations for estimation of RMR (kcal) = 589.009 + [(8.846 x weight (kg)] + [(9.939 x FFM (kg)] + [(65.205 x sex (male=1, female=0)]. RMR (p<0.05) and FM (p<0.001) was significantly associated with IR. Findings of this study provides accurate estimates of TBW and FFM in Malaysian children and can be recommended as useful tool in providing better understanding of nutritional status and body composition among children.